2014
DOI: 10.1371/journal.pone.0098938
|View full text |Cite
|
Sign up to set email alerts
|

The Human Antibody Response to the Surface of Mycobacterium tuberculosis

Abstract: BackgroundVaccine-induced human antibodies to surface components of Haemophilus influenzae and Streptococcus pneumonia are correlated with protection. Monoclonal antibodies to surface components of Mycobacterium tuberculosis are also protective in animal models. We have characterized human antibodies that bind to the surface of live M. tuberculosis.MethodsPlasma from humans with latent tuberculosis (TB) infection (n = 23), active TB disease (n = 40), and uninfected controls (n = 9) were assayed by ELISA for re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 38 publications
4
38
0
Order By: Relevance
“…This finding is supported by several other studies that found higher levels of anti-LAM IgG in HIV-negative patients with TB, compared to controls with a positive TST result [22,23]. The study of Perley et al showed that anti-LAM titers were similar among healthy, latent and active TB subjects, however LTBI subjects had avidity intermediate between uninfected controls and active TB patient [24]. In the same study, the MAC positivity in studied groups was not clearly described, therefore the possible antibody cross reaction between species could not be excluded.…”
Section: Discussionsupporting
confidence: 59%
“…This finding is supported by several other studies that found higher levels of anti-LAM IgG in HIV-negative patients with TB, compared to controls with a positive TST result [22,23]. The study of Perley et al showed that anti-LAM titers were similar among healthy, latent and active TB subjects, however LTBI subjects had avidity intermediate between uninfected controls and active TB patient [24]. In the same study, the MAC positivity in studied groups was not clearly described, therefore the possible antibody cross reaction between species could not be excluded.…”
Section: Discussionsupporting
confidence: 59%
“…Early after antimycobacterial therapy for M. tuberculosis infections in humans, there is a decrease in antibody avidity accompanied by an initial increase in serum antibody levels, likely due to the bactericidal activity of antituberculous drugs leading to low-affinity antibodies to released antigens (38). Also, humans with active tuberculosis produce low-avidity antibodies with low IgG/IgM ratios for surface antigens of M. tuberculosis but higher-avidity antibodies with higher IgG/IgM ratios for cellular fractions of antigens, potentially indicating immune evasion strategies of this highly successful pathogen, given the association with protection for highly avid antibodies to surface components of other bacteria (39). With experimental M. bovis infection, the disease is generally considered slowly progressive (40,41), thus most closely resembling the active form of the disease in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Although it was known that both active TB patients and healthy subjects make detectable antibody responses to Mtb (19)(20)(21), it was not known whether any of these antibodies afford direct protection against infection. We decided to test total antibody from our subjects in a mouse protection assay (Fig.…”
Section: Significancementioning
confidence: 99%